Interannual Changes in the Prevalence of Intimate Partner Violence Against Pregnant Women in Miyagi Prefecture After the Great East Japan Earthquake: The Japan Environment and Children's Study. Issue 21 (November 2021) - Tanoue, Kaou; Nishigori, Hidekazu; Watanabe, Zen; Tanaka, Kosuke; Sakurai, Kasumi; Mizuno, Satoshi; Ishikuro, Mami; Obara, Taku; Tachibana, Masahito; Hoshiai, Tetsuro; Saito, Masatoshi; Sugawara, Junichi; et al.
This study aimed to clarify the interannual changes in intimate partner violence against pregnant women after the March 11, 2011 Great East Japan Earthquake in target areas of Miyagi Prefecture that were damaged by the earthquake and tsunami. Because of this disaster, in Miyagi Prefecture, approximately 12, 000 people died or went missing, and approximately 238, 000 buildings were destroyed. According to the U.S. Geological Survey, the Great East Japan Earthquake is the fourth largest earthquake in the world and the largest in Japan since 1900. The present study was part of the Japan Environment and Children's Study. Data from June 2011 to May 2014 of 79, 222 pregnant women were analyzed, calculating the prevalence of physical and mental intimate partner violence in the inland, north coastal, and south coastal areas of Miyagi. These prevalence rates were compared with nationwide rates of intimate partner violence in 2011 using univariate and logistic regression analyses. After the disaster, the incidence of mental intimate partner violence increased in the south coastal area and then improved later (19.4%, 13.1%, and 13.3% for south coastal area, and 13.8%, 13.8%, and 13.1% for nationwide in 2011, 2012, and 2013, respectively). However, in the north coastal area, the incidence of physical intimate partner violence increased after the disaster and then improved later (2.7%, 1.5%, and 1.3% for north coastal area, and 1.4%, 1.3%, and 1.1% for nationwide in 2011, 2012, and 2013, respectively). In the inland area, however, the prevalence of both mental and physical intimate partner violence was consistently higher than nationwide rates after the disaster.